Palaeoclimatic implications of high-resolution clay mineral assemblages preceding and across the onset of the Palaeocene–Eocene Thermal Maximum, North Sea Basin. (2nd January 2018) - Kemp, Simon J.; Ellis, Michael A.; Mounteney, Ian; Kender, Sev
Abstract: Understanding the composition of clay-rich sediments and their transportation into proximal marine basins allows us to better decipher hydroclimatic changes before and within the Palaeocene–Eocene Thermal Maximum (PETM). Only a limited number of such studies exists from the North Sea Basin, which was proximal to the volcanic activity and early rifting hypothesized to have triggered the PETM. The present study examines core material from well 22/10a-4, UK North Sea, as it exhibits an exceptionally expanded and almost stratigraphically complete fine-grained sedimentary sequence suitable for high-resolution analysis. Quantitative Newmod-for-Windows ™-modelled clay mineral assemblages, rather than traditional semi-quantitative estimates, are dominated by smectite-rich, interlayered illite-smectite that probably developed from volcanogenic deposits on continental landmasses. Soil development before the PETM is consistent with the existence of a seasonal tropical climate with a prolonged dry season. A striking rise and fall of kaolinite content within the PETM onset, prior to the principal carbon-isotope excursion, is reported here. This variation is interpreted as a signal of an enhanced hydrologic cycle producing an increase in erosionally derived kaolinite, followed by a dampening of this detrital source as sea-levels rose. Global variations in PETM kaolinite concentrations are consistent with a latitudinal shift in patterns of precipitation in models of global warming.